METHODS OF PROVIDING SOCIO PSYCHOLOGICAL ASSISTANCE TO ADOLESCENTS IN EXTREME SITUATIONS (Web of Teachers: Inderscience Research, 2025)
This article explores effective methods for providing socio-psychological assistance to adolescents experiencing extreme situations. It examines psychological distress, intervention techniques, and best practices in supporting adolescent mental health. The study highlights crisis intervention strategies, therapeutic approaches, and the role of social support systems. Findings suggest that a multidisciplinary approach, integrating psychological counseling and social assistance, is crucial for helping adolescents cope with traumatic experiences.